Interactive media for autism students - Rafie, Siti Khadijah; Rahim, Azira; Ahmad, Nabila; Abas, Nurliyana (Universiti Teknologi MARA, Kedah, 2018)
Interactive media developed as a teaching and learning tools for the autism students. It was due to the children that have autism problem identified by various characteristics, and it is very challenging for the teachers to capture their focus. Interactive media on healthy lifestyle and few subjects was developed in order to teach them in an interesting way. The media was shown to students of Sekolah Rendah Pendidikan Khas Merbok, Sungai Petani. It shown that they are attracted to the media and another media on other moral values will be developed in future and it will be proposing to Ministry of Education as the syllabus for Sekolah Pendidikan Khas in Malaysia. Novelty and uniqueness: There is no interactive media for the special needs students yet. After few sessions of showing the video to them, students seem very interested to learn and they are engaged in class. The video was developed according to the students‟ ability. It is not complicated and attractive enough to the students.